Análisis de la propiedad, planta y equipo: partida vehículos de la Universidad Técnica de Babahoyo - Tuapanta Curi, Jorge Luis (2019)
In the present case study an analysis of the Property, plant and equipment will be developed, specifically in the vehicle heading at the Technical University of Babahoyo. Several research techniques are used for the development of this study in the Departments of the institution responsible for the accounting treatment of the Vehicles item. After having collected and examined the information, it was found that there are several of these assets that have already fulfilled their useful life in addition to the revaluation of the vehicle item is not updated. The only accounting process that has received the item Vehicle is the depreciation, therefore, the values of the account to be outdated in the real situation in its financial statements of the institution